THE CONTENT OF THE INTEGRATED EDUCATIONAL ENVIRONMENT IN THE PREPARATION OF MEDICAL STUDENTS FOR PROFESSIONAL ACTIVITY - Khalikova Oyista Yuldashevna (Web of Journals Publishing, 2025)
The article emphasizes the value of the "Technical school-HE" integrated environment in teaching medical science at medical technical schools, the advantages of organizing in the integrated educational environment, and the contents of the various elements that comprise the integrated environment.
Keywords: Pedagogy, integration, innovation, creativity, motivation, competence, non-traditional lesson, binary lesson, dual education, medical education.